Key words in religion, media and culture - Morgan, David (Routledge, 2008)
'From The Passion of the Christ to the presumed 'clash of civilizations', religion's role in culture is increasingly contested and mediated. Key Words in Religion, Media, and Culture is a welcome and interdisciplinary contribution that maps the territory for those who aim to make sense of it all. Highlighting the important concepts guiding state-of-the-art research into religion, media, and culture, this book is bound to become an important and frequently consulted resource among scholars both seasoned and new to the field.' - Lynn Schofield Clark , author of From Angels to Aliens: Teenagers